Speeding of oxygen uptake kinetics is not different following low-intensity blood-flow-restricted and high-intensity interval training - Corvino, Rogerio B.; Oliveira, Mariana F. M.; Denadai, Benedito S. [UNESP]; Rossiter, Harry B.; Caputo, Fabrizio (Wiley-Blackwell, 2019)
New Findings What is the central question of this study? Can interval blood-flow-restricted (BFR) cycling training, undertaken at a low intensity, promote a similar adaptation to oxygen uptake (V?O2) kinetics to high-intensity interval training? What is the main finding and its importance? Speeding of pulmonary V?O2 on-kinetics in healthy young subjects was not different between low-intensity interval BFR training and traditional high-intensity interval training. Given that very low workloads are well tolerated during BFR cycle training and speed V?O2 on-kinetics, this training method could be used when high mechanical loads are contraindicated. Low-intensity blood-flow-restricted (BFR) endurance training is effective to increase aerobic capacity. Whether it speeds pulmonary oxygen uptake (V?O2p), CO2 output (V?CO2p) and ventilatory (V? Ep ) kinetics has not been examined. We hypothesized that low-intensity BFR training would reduce the phase 2 time constant (tau(p)) of V?O2p, V?CO2p and V? Ep by a similar magnitude to traditional high-intensity interval training (HIT). Low-intensity interval training with BFR served as a control. Twenty-four participants (25 +/- 6 years old; maximal V?O2 46 +/- 6 ml kg(-1) min(-1)) were assigned to one of the following: low-intensity BFR interval training (BFR; n = 8); low-intensity interval training without BFR (LOW; n = 7); or high-intensity interval training without BFR (HIT; n = 9). Training was 12 sessions of two sets of five to eight x 2 min cycling and 1 min resting intervals. LOW and BFR were conducted at 30% of peak incremental power (P-peak), and HIT was at similar to 103% P-peak. For BFR, cuffs were inflated on both thighs (140-200 mmHg) during exercise and deflated during rest intervals. Six moderate-intensity step transitions (30% P-peak) were averaged for analysis of pulmonary on-kinetics. Both BFR (pre- versus post-training tau(p) = 18.3 +/- 3.2 versus 14.5 +/- 3.4 s; effect size = 1.14) and HIT (tau(p) = 20.3 +/- 4.0 versus 13.1 +/- 2.9 s; effect size = 1.75) reduced the V?O2p tau(p) (P < 0.05). As expected, there was no change in LOW (V?O2p tau(p) = 17.9 +/- 6.2 versus 17.7 +/- 4.3 s; P = 0.9). The kinetics of V?CO2p and V? Ep were speeded only after HIT (38.5 +/- 10.6%, P < 0.001 and 31.2 +/- 24.7%, P = 0.004, respectively). Both HIT and low-intensity BFR training were effective in speeding moderate-intensity V?O2p kinetics. These data support the findings of others that low-intensity cycling training with BFR increases muscle oxidative capacity.
Keywords: cycling; endurance training; exercise; gas exchange